METHODOLOGICAL SUPPORT OF SENIOR SCHOOL STUDENTS IN THE PROCESS OF TEACHING BASKETBALL (ON THE EXAMPLE OF PHYSICAL EDUCATION CLASSES) (Web of Teachers: Inderscience Research, 2026)
This article analyzes the provision of methodological support for basketball teachers working with 11th-grade students. It highlights the importance of physical education classes, the development of a healthy lifestyle, and the formation of students’ physical strength and volitional qualities. Experimental research was conducted involving physical education teachers, including the application of individual and group approaches, the development of methodological support materials, as well as the design and implementation of a monitoring system to assess students’ acquisition of knowledge and skills.